Analisis Studi Kelayakan Bisnis Pada Usaha Coffee Shop Mahoni Coffee di Kota Medan - Vientiany, Dini; Batubara, Alwi Ardiansyah Putra; Salsabil, Hafiz; Angkasa, Pramuja (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
A business feasibility study is a crucial step in assessing the viability of a business before it is launched or developed sustainably. This study aims to analyze the feasibility of Mahoni Coffee, a coffee shop located at Jalan Mahoni No. 20, East Medan District, Medan City. The analysis was conducted comprehensively by reviewing various aspects, including market and marketing aspects, legal aspects, technical and operational aspects, and management aspects. The method used in compiling this study is a qualitative descriptive method with data collection through direct observation, mini-surveys with consumers, and relevant literature studies. The analysis shows that Mahoni Coffee has clear market potential, a strategic location, a business concept that aligns with the needs of young consumers, and a profitable financial outlook. Furthermore, the implementation of Sharia principles, a commitment to halal product certification, and concern for environmental and social aspects add value to the business's sustainability. Based on these analysis results, it can be concluded that Mahoni Coffee is a viable business for future development.